2021
DOI: 10.1007/978-3-030-67835-7_28
|View full text |Cite
|
Sign up to set email alerts
|

Mobile eHealth Platform for Home Monitoring of Bipolar Disorder

Abstract: People suffering Bipolar Disorder (BD) experiment changes in mood status having depressive or manic episodes with normal periods in the middle. BD is a chronic disease with a high level of non-adherence to medication that needs a continuous monitoring of patients to detect when they relapse in an episode, so that physicians can take care of them. Here we present MoodRecord, an easy-to-use, non-intrusive, multilingual, robust and scalable platform suitable for home monitoring patients with BD, that allows physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The algorithmic apparatus that is described in [28] has been considered during the specification of the integrated data management system's data processing components [29,30]. Nevertheless, the comprehensive validity assessment that we conducted [31] showed that even the optimized homomorphic encryption models are not feasible [32] for the timely processing of the acquired medical data on the mobile client devices [33]. Moreover, it is significant to mention the relevant contributions that pertain to the realm of ubiquitous systems.…”
Section: Relevant Existing Contributions and Essential Research Gapsmentioning
confidence: 99%
“…The algorithmic apparatus that is described in [28] has been considered during the specification of the integrated data management system's data processing components [29,30]. Nevertheless, the comprehensive validity assessment that we conducted [31] showed that even the optimized homomorphic encryption models are not feasible [32] for the timely processing of the acquired medical data on the mobile client devices [33]. Moreover, it is significant to mention the relevant contributions that pertain to the realm of ubiquitous systems.…”
Section: Relevant Existing Contributions and Essential Research Gapsmentioning
confidence: 99%
“…[ 36 ] may be used during the design of data processing components that are part of relevant integrated data management systems [ 37 ]. It is important to note that the comprehensive validity evaluation that we conducted [ 34 ] proves that even certain improved homomorphic encryption approaches are not adequate [ 51 , 52 ] relative to the timely processing of the collected medical data on the client side [ 35 , 53 ]. Furthermore, it is important to note the papers [ 54 , 55 ] that are connected to the full scope of ubiquitous systems.…”
Section: Data Acquisition Through Mobile Devices and Sensorsmentioning
confidence: 99%
“…Instead, the NYMPHA-MD project 11 defined a framework for continuous patient monitoring to identify early warning signs of deviations in mood and attitudes suggesting the onset of a depressive or maniac episode, which, in turn, will allow for early intervention. 12 PULSO Ediciones S.L. won the NYMPHA-MD Pre-Commercial Procurement bid with the MoodRecord project, where the Universitat Pompeu Fabra (Barcelona) developed the speech module analysis.…”
Section: Introductionmentioning
confidence: 99%